2020
DOI: 10.1186/s12903-020-01205-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and volumetric outcomes after vertical ridge augmentation using computer-aided-design/computer-aided manufacturing (CAD/CAM) customized titanium meshes: a pilot study

Abstract: Background One of the most recent innovations in bone augmentation surgery is represented by computer-aided-design/computer-aided-manufacturing (CAD/CAM) customized titanium meshes, which can be used to restore vertical bone defects before implant-prosthetic rehabilitations. The aim of this study was to evaluate the effectiveness/reliability of this technique in a consecutive series of cases. Methods Ten patients in need of bone augmentation before implant therapy were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 40 publications
1
57
1
Order By: Relevance
“…With traditional manually created titanium meshes, the exposure range is extensive (0–68.9%) (Lizio et al, 2014; Pieri et al, 2008; Poomprakobsri et al, 2021). Ciocca et al, using digitally customized meshes, reported 66% of postoperative exposure morbidity in nine cases (Ciocca et al, 2018), and Li et al reported 25% morbidity in 16 patients (Li et al, 2021); Chiapasco et al reported 11 exposure cases in 53 dehiscence cases (Chiapasco et al, 2021), and Cucchi et al recorded one in 10 cases (Cucchi et al, 2020). Sumida et al, comparing two groups of 13 patients, found one and three exposures for CAD/CAM and traditional devices, respectively (Sumida et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With traditional manually created titanium meshes, the exposure range is extensive (0–68.9%) (Lizio et al, 2014; Pieri et al, 2008; Poomprakobsri et al, 2021). Ciocca et al, using digitally customized meshes, reported 66% of postoperative exposure morbidity in nine cases (Ciocca et al, 2018), and Li et al reported 25% morbidity in 16 patients (Li et al, 2021); Chiapasco et al reported 11 exposure cases in 53 dehiscence cases (Chiapasco et al, 2021), and Cucchi et al recorded one in 10 cases (Cucchi et al, 2020). Sumida et al, comparing two groups of 13 patients, found one and three exposures for CAD/CAM and traditional devices, respectively (Sumida et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis stated exposure rates of 31% with custom‐made meshes and 51% with conventional meshes (Zhou et al, 2021). Comparing the actual bone volumes with digitally planned bone volumes from CAD/CAM procedures, Cucchi et al and Chiapasco et al reported technique reliability rates of 89% and 91.9%, respectively (Chiapasco et al, 2021; Cucchi et al, 2020). These results are consistent with Li et al, recording 95.82% reliability (range: 88.53%–99.15%) (Pellegrino et al, 2021), but higher than Lizio et al, with a 69.8% of obtained bone, both using meshes preformed on stereo‐lithographic models (Lizio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Intraoral scanning offers reduced chairside time and improved patient comfort, compared to conventional impression making [7]. Moreover, intraoral scanning in conjunction with cone-beam computed tomography (CBCT), 3D printing, and extraoral face scans can assist in creating a virtual dental patient image and possibly offer a more streamlined and accurate digital workflow for dental care delivery [4,16]. On the other hand, a possible limitation of the technique is the need to ensure that a strict and standardised protocol is followed in acquiring the scans.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have previously used in-vivo cone beam computed tomographic (CBCT) scanning or extraoral surface scanning of patient casts to monitor and quantify bone remodelling up to four months post-extraction [2,3]. Indeed, a recent study involving ten patients demonstrated the use of CBCT to measure volumetric changes post vertical ridge augmentation in the form of vertical bone gain, planned bone volume, lacking bone volume, and regenerated bone volume, using computer-aided design/computer-aided manufacturing customised titanium meshes [4]. However, CBCT scans carry the disadvantage of radiation exposure, whereas dental stone casts undergo linear expansion over time that can significantly affect their accuracy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple recent studies have reported favorable vertical and horizontal linear bone gain at sites augmented with customized titanium mesh [ 9 , 15 ]. A recent study by Cucchi et al also evaluated augmentation with customized titanium mesh volumetrically in 10 patients, reporting an average of 89% regeneration of defect area [ 16 ]. The aims of this prospective pilot study were threefold: (1) to compare pre- and post-treatment CBCT scans to determine the volume of radiographic bone fill attained, (2) to assess surgical accuracy of the placement of the CTRAM compared to the digitally planned location, and (3) to record bone fill clinically by comparing pre- and post-surgical probing measurements at designated points from the surface of the CTRAM to the underlying bone.…”
Section: Introductionmentioning
confidence: 99%